2013
DOI: 10.1007/s11010-013-1786-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-335 suppresses migration and invasion by targeting ROCK1 in osteosarcoma cells

Abstract: Accumulating evidence has shown that microRNAs are involved in multiple processes in cancer development and progression. Recently, miR-335 has been identified as a tumor-suppressing microRNA in many human cancers. However, the specific function of miR-335 in osteosarcoma is unclear at this point. In this study, we found that the expression of miR-335 in osteosarcoma tissues and cell lines was much lower than that in normal control, respectively, and the downregulated miR-335 was significantly associated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 27 publications
5
82
0
2
Order By: Relevance
“…Based on bioinformatical predication, a luciferase reporter assay was performed and PAX6 was identified as a novel target of miR-335, which has been demonstrated to be implicated in various types of cancer (14)(15)(16)(17)(18)(19)(20)(21)(22). However, the detailed role of miR-335 in the development and progression of various types of cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on bioinformatical predication, a luciferase reporter assay was performed and PAX6 was identified as a novel target of miR-335, which has been demonstrated to be implicated in various types of cancer (14)(15)(16)(17)(18)(19)(20)(21)(22). However, the detailed role of miR-335 in the development and progression of various types of cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed role of miR-335 in the development and progression of various types of cancer remains controversial. For instance, it has been suggested that miR-335 may function as a tumor suppressor in osteosarcoma (14), however, it may act as an oncogene in meningiomas (21). These findings suggest that the exact regulatory function of miR-335 in tumorigenesis is tissue specific, since different microenvironments in various types of cancer may have different effects on the expression and activity of miR-335.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, increased levels of miR-128 are negatively correlated with PTEN levels, and increased proliferation of MG63 and U2OS OS cells (28). In contrast to these oncogene-like miRNA functions, miR-335 and miR-340 function as tumor suppressors by targeting the Rho-associated, coiled-coil containing protein kinase 1 gene and, thereby, inhibit OS cell migration and invasion (29,30). miR-126 inhibits the proliferation of OS cells by targeting sirt1, a histone deacetylase (31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have employed qRT-PCR for osteosarcoma research. For instance, down-regulation of miR-335 is significantly associated with lymph node metastasis, indicating that this miRNA inhibits cell migratory and invasive properties [79] .…”
Section: Mirna Analysismentioning
confidence: 99%